Faith-Based Environmentalism: Sahal Mahfudz and the Ecological Transformation of Pesantren - Ma'rufah, Hafidhoh (Jurnal Sosiologi Reflektif, 2025)
Islamic boarding schools (pesantren) in Indonesia, as part of civil society, have played a significant role in addressing various contemporary social issues, including environmental challenges. While several studies have explored pesantren engagement with ecological issues, the environmental thought of Sahal Mahfudz, particularly its connection to his concept of fiqh sosial and Islamic eco-theology remains underexplored. This study aims to examine the sociological ideas of Sahal Mahfudz in responding to environmental challenges through the institution of pesantren. This study employs a qualitative method with a literature review approach, collecting data from Sahal Mahfudz’s works related to environmental issues, as well as secondary data from various scholarly literature, articles, and other media sources. Data analysis was conducted using thematic and interpretive analysis techniques. The findings reveal that Sahal Mahfudz integrates Islamic theological principles, such as khalifah (stewardship) and ibadatullah (worship) with social responsibility, positioning pesantren as transformative agents for ecological preservation through tradition, dialogue, and community-based action. The implications of this study highlight the importance of strengthening pesantren capacity to foster ecological consciousness and practices, and suggest that fiqh sosial can be further developed into an interdisciplinary framework bridging theology, sociology, and environmental studies. Pesantren di Indonesia sebagai bagian dari civil society telah berperan dalam menghadapi berbagai isu sosial kontemporer, termasuk masalah lingkungan hidup. Meskipun sejumlah studi telah membahas keterlibatan pesantren dalam isu-isu ekologi, pemikiran Sahal Mahfudz mengenai lingkungan, terutama keterkaitannya dengan konsep fiqh sosial dan praktik ekoteologi Islam, masih jarang dieksplorasi. Penelitian ini bertujuan untuk mengkaji ide-ide sosiologis Sahal Mahfudz dalam merespons tantangan lingkungan melalui peran pesantren. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi pustaka, data dikumpulkan dari karya-karya Sahal Mahfudz yang berkaitan dengan lingkungan hidup, serta data sekunder dari berbagai literatur ilmiah, artikel, dan media lainnya. Teknik analisis data menggunakan analisis tematik dan interpretif. Temuan penelitian menunjukkan bahwa Sahal Mahfudz mengintegrasikan nilai-nilai teologis Islam, seperti konsep khalifah dan ibadatullah dengan tanggung jawab sosial, membentuk pesantren sebagai agen transformasi ekologi berbasis tradisi, dialog, dan aksi komunitas. Implikasi penelitian ini menekankan pentingnya memperkuat kapasitas pesantren dalam membangun kesadaran dan praksis ekologis, serta mendorong pengembangan fiqh sosial sebagai kerangka interdisipliner yang menghubungkan teologi, sosiologi, dan studi lingkungan.